Rat umbilical cord derived stromal cells maintain markers of pluripotency: Oct4, Nanog, Sox2, and alkaline phosphatase in mouse embryonic stem cells in the absence of LIF and 2‐MCE - Hong, James S. (Kansas State University, 2009)
When mouse embryonic stem cells (ESCs) were grown on mitotically inactivated rat umbilical cord-derived stromal cells (RUCs) in the absence of leukemia inhibitory factor (LIF) and 2-mercaptoethanol (2-MCE), the ESCs showed alkaline phosphatase (AP) staining. ESCs cultured on RUCs maintain expression of the following pluripotency genes, Nanog, Sox2 and Oct4 and grow at a slower rate when compared with ESCs grown on mitotically inactivated mouse embryonic fibroblasts (MEFs). Differences in gene expression for the markers of pluripotency Oct4, Sox2 and Nanog, AP staining and ESC growth rate were also observed after LIF and 2-MCE were removed from the co-cultures. Reverse transcriptase polymerase chain reaction (RT-PCR) suggested differences in Sox2 and Nanog mRNA expression, with both genes being expressed at higher levels in the ESCs cultured on RUCs in the absence of LIF/2-MCE as compared to ESCs cultured on MEFs. Semi-quantitative RT-PCR indicated that Nanog expression was higher when ESCs were grown on RUCs in the absence of LIF and 2-MCE as compared to MEFs in the same treatment conditions. Bisulfite-mediated methylation analysis of the Nanog proximal promoter suggested that the maintenance of Nanog gene expression found in ESCs grown on RUCs after culture for 96 hours in the absence of LIF/2-MCE may be due to prevention of methylation of the CpG dinucleotides in the Nanog proximal promoter as compared to ESCs grown on MEFs. Thus, RUCs may release factors into the medium that maintain the pluripotent state of mouse ESCs in the absence of LIF and 2-MCE.
Keywords: Mouse embryonic stem cell physiology; embryonic stem cell pluripotency maintenance; epigenetic regulation of pluripotency; cell culture; Biology, Cell (0379); Biology, Molecular (0307); Biology, Veterinary Science (0778)